Sources of macroeconomic fluctuations: A regime-switching DSGE approach - Zheng Liu; Daniel F. Waggoner; Tao Zha (Federal Reserve Bank of Atlanta, 2010)
We examine the sources of macroeconomic economic fluctuations by estimating a variety of medium-scale DSGE models within a unified framework that incorporates regime switching both in shock variances and in the inflation target. Our general framework includes a number of different model features studied in the literature. We propose an efficient methodology for estimating regime-switching DSGE models. The model that best fits the U.S. time-series data is the one with synchronized shifts in shock variances across two regimes and the fit does not rely on strong nominal rigidities. We find little evidence of changes in the inflation target. We identify three types of shocks that account for most of macroeconomic fluctuations: shocks to total factor productivity, wage markup, and the capital depreciation rate.
Keywords: C11; C51; E32; E42; E52; 330; systematic analysis; regime switching; depreciation shock; efficient estimation methods; Dynamisches Gleichgewicht; Inflation Targeting; Schock; Geldpolitik; Konjunkturpolitik; Theorie; USA